2018
DOI: 10.1016/j.ajpath.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Stimulates Brain-Derived Neurotrophic Factor Production in Eutopic Endometriosis Stromal Cell Cultures

Abstract: Endometriosis implants are comprised of glandular and stromal elements, macrophages, nerves, and blood vessels and are commonly accompanied by pelvic pain. We propose that activated macrophages are recruited to and infiltrate nascent lesions, where they secrete proinflammatory cytokines, promoting the production of chemokines, neurotrophins, and angiogenic growth factors that sustain an inflammatory microenvironment. Immunohistochemical evaluation of endometriosis lesions reveals in situ colocalization of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 66 publications
1
32
0
3
Order By: Relevance
“…IL-1β also contributes to recruitment of macrophages and neuroangiogenesis by regulating chemokine RANTES and promoting the production of brain-derived neurotrophic factor (BDNF), which co-localizes with macrophages and nerve fibers in endometriotic lesions and cultures of eutopic stromal cells; both events are mediated through c-Jun N-terminal kinase (JNK) and NF-κB signaling pathways. These findings support the notion of interaction between pro-inflammatory factors that favor the communication between different cell types in endometriotic lesions, which as a result promote the recruitment of vessels and nerves to stimulate angiogenesis, growth of the lesion, and generation of pain (40).…”
Section: Alterations Of Immune Mediatorssupporting
confidence: 86%
See 2 more Smart Citations
“…IL-1β also contributes to recruitment of macrophages and neuroangiogenesis by regulating chemokine RANTES and promoting the production of brain-derived neurotrophic factor (BDNF), which co-localizes with macrophages and nerve fibers in endometriotic lesions and cultures of eutopic stromal cells; both events are mediated through c-Jun N-terminal kinase (JNK) and NF-κB signaling pathways. These findings support the notion of interaction between pro-inflammatory factors that favor the communication between different cell types in endometriotic lesions, which as a result promote the recruitment of vessels and nerves to stimulate angiogenesis, growth of the lesion, and generation of pain (40).…”
Section: Alterations Of Immune Mediatorssupporting
confidence: 86%
“…Inflammation in endometriosis is generally attributed to the recruitment of macrophages and other activated leukocytes from bone marrow to the developing endometriotic lesions and eutopic endometrium, these cells are attracted by chemokines synthesized and released in situ. In the endometriotic lesions, immune cells secrete elevated levels of pro-inflammatory cytokines, which in turn stimulate the production of diverse molecules such as chemokines, and growth factors that sustain an inflammatory microenvironment and the remodeling of the ectopic tissue (40). This tissue also has the capacity of releasing pro-inflammatory factors, creating a positive feedback loop that maintains the chronic inflammation state (57).…”
Section: Alteration Of Immune Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these diseases and gout, IL-1 is an important factor causing strong pain. Indeed, recently Yu et al reported that a potential of IL-1β in neuroangiogenesis by the induction of brain-derived neurotrophic factor from eutopic endometriosis stromal cells (8). Suppression of IL-1 may provide effective treatment against pelvic pain caused by endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the reflux of menstrual blood is observed in most women, endometriosis cannot be explained by reflux alone. In addition, inflammatory cytokines, such as tumor necrosis factor α (5, 6), interleukin (IL)-1β (7, 8), and IL-33 (9), and immune cells, such as macrophages (10) and natural killer cells (11, 12), were reported to be involved in the pathogenesis of endometriosis. However, limited studies have investigated the mechanism of their actions in endometriosis.…”
Section: Introductionmentioning
confidence: 99%